2,6-bis(5-(2,2-dimethylpropyl)-1H-pyrazol-3-yl)pyridine as a ligand for efficient actinide(III)/lanthanide(III) separation - Bremer, Antje; Ruff, Christian; Panak, Petra (Inorganic chemistry, 2012)
The N-donor complexing ligand 2,6-bis(5-(2,2-dimethylpropyl)-1H-pyrazol-3-yl)pyridine (C5-BPP) was synthesized and screened as an extracting agent selective for trivalent actinide cations over lanthanides. C5-BPP extracts Am(III) from up to 1 mol/L HNO3 with a separation factor over Eu(III) of approximately 100. Due to its good performance as an extracting agent, the complexation of trivalent actinides and lanthanides with C5-BPP was studied. The solid-state compounds [Ln(C5-BPP)(NO3)3(DMF)] (Ln = Sm(III), Eu(III)) were synthesized, fully characterized, and compared to the solution structure of the Am(III) 1:1 complex [Am(C5-BPP)(NO3)3]. The high stability constant of log β3 = 14.8 ± 0.4 determined for the Cm(III) 1:3 complex is in line with C5-BPP’s high distribution ratios for Am(III) observed in extraction experiments.
Published: April 19, 2012
Gesehen am 28.06.2018